9 - Des cimetières lotis à Kisangani : exemple d’un débat occulte sur la gestion des espaces publics en RDC: https://doi.org/10.4314/ad.v35i4.70222 - Ndemba, Roger Ekongo (Africa Development, 2021)
In the major cities of the DRC, as in those of most African countries, cemeteries are public spaces managed by the municipalities. Formerly spaces reserved for the dead and objects of respect, regular upkeep and protection of all kinds, these sites have now fallen prey to irresponsible management on the part of the public authorities. Public debates on the issue are virtually invisible. In Kisangani, the transformation of many cemeteries still in use into places of residence comes close to a profanation of those sites. The living and the dead are side by side. Beyond the issues of health and public hygiene, this cohabitation also raises the issue of revolution in beliefs and mentalities as well as the issue of the inefficiency of public policy in terms of urban planning. A public debate on this issue, notably thanks to a strong and dynamic civil society and accountable public authorities, would make it possible to end the trivialization of the ‘sacred’ nd the ‘mystical’ as well as the irresponsible management of our public spaces.